ANALISIS TATA KELOLA PELAKSANAAN SUPERVISI PENDIDIKAN DI SDN 4 PASANGGRAHAN GARUT - Elsa Muslihatunnisa; Karantiano S Putra; Mohamad Ramdan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is one of the most important elements in human life which is a process of forming human personality and character. Elementary school management must be implemented effectively and professionally, through good educational governance, governance is an activity carried out in a structured and systematic manner in compiling, planning, analyzing, and establishing plans in order to achieve the stated goals. Principal supervision is one of the important factors in improving the quality of elementary school management. This study aims to analyze the implementation of principal supervision in improving the quality of school management at SDN 4 Pasanggrahan Garut which includes aspects of supervision governance, supporting factors for supervision effectiveness, obstacles faced, and efforts to improve the quality of supervision. This study uses a qualitative approach, descriptive method using observation and interview data collection techniques with the principal research subjects. The results of this study indicate that the implementation of principal supervision at SDN 4 Pasanggrahan Garut has been implemented well, directed and programmed through the planning stage, implementation stage, and evaluation stage. Factors that support the effectiveness of educational supervision are: Commitment and leadership of the principal, teacher involvement, availability of resources, an effective and sustainable evaluation reporting system and parental involvement in supervision activities. Not only that, supervision at SDN 4 Pasanggrahan Garut also faces obstacles that can hinder the effectiveness in improving the quality of learning, such as difficulty managing time so as not to clash with other activities. Efforts that the school can make in implementing supervision include: the principal trying to understand the problem and solve the problem and provide solutions to something that is lacking, facilitating teachers to participate in training, such as seminars or workshops and providing adequate facilities and infrastructure. Thus, the implementation of principal supervision plays a vital role in improving the quality of elementary school management.